Curry. Issue 4 (4th July 2017) - Varman, Rohit
ABSTRACT: Marketplace icons are often markers of transnational transactions engendered by commercialization and dominance of the West. Curry as a marketplace icon helps to identify these constituents of iconicity. This article briefly examines the historical roots of curry or spicy Indian food and its implication in the project of colonialism. Curry as a signifier of Indian food was invented in British colonial narratives and shaped by commercial interests and racial prejudices. Because of the way forces of colonization and commercialization create international circulation of goods and ideas through globalization, curry as a marketplace icon signifies hegemony and global hierarchies that shape ideas of consumption and markets.